Copyright issues in managing information - Khaw, Lake Tee, Professor (PETRONAS, 2010)
Organized by PETRONAS in collaboration with Pustaka Sumber Ilmu, 15th – 17th May 2005 at Nikko Hotel Kuala Lumpur, Malaysia.